Pengaruh Penggunaan Pendekatan Keterampilan Proses Terhadap Hasil Belajar Materi Tumbuhan Hijau di Kelas V Sekolah Dasar - Viyanti, Erva; Desyandri, Desyandri; Zen, Mulyani (Universitas Negeri Padang, 2014)
The purpose of this research was to determine the effect of the use of process skills approach to the learning outcomes of green plant material in the fifth grade. Types of this research was an experimental research with a quasi-experimental design and form design posttest only control group design. Population of this research was all students in the fifth grade. Sampling technique using saturated sampling. These samples included 52 people. Instrument of this research was used a test. Based on the test results of normality and homogenity of the posttest data, known both classes of data samples have normal distribution and homogeneous variance. After that, from the calculation hypothesis test obtained tprice of 2.23 and a price ttable with t(0.05; 50) at a significance level of 0.05 and df = 50 is 2.00856. These results indicate that the tprice > ttable, so H0 was rejected and Ha acceptable. Therefore, it can be concluded that there is significant effect in the use of process skills approach to the learning outcomes of green plant material in the fifth grade.